2012
DOI: 10.1111/j.1755-3768.2011.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in West Africa: is couching still a choice?

Abstract: epidemiology of PCV among Scandinavians has yet been available. Our study is the first to discover that PCV is not rare in a lightly pigmented homogeneous Scandinavian population. We found out that 8% of the patients presenting with presumed neovascular AMD actually had PCV. This may seem somewhat surprising as most reports on PCV emanate from clinics dealing with mixed or pigmented populations. Omission of ICG angiography from the investigational strategy irrefutably leads to underestimation of PCV and, conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This may be explained by incomplete execution of eye care programmes at a national level, poor patient education and outdated practices such as “couching,” and restricted resource allocation to eye care due to competing health issues. This has furthermore resulted in reduced access to eye care providers, from patients being informally charged for surgeons' additional salary compensation …”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by incomplete execution of eye care programmes at a national level, poor patient education and outdated practices such as “couching,” and restricted resource allocation to eye care due to competing health issues. This has furthermore resulted in reduced access to eye care providers, from patients being informally charged for surgeons' additional salary compensation …”
Section: Discussionmentioning
confidence: 99%
“…Although the WHO recommendations for visual improvement after cataract surgery implies higher levels of CDVA, it has been reported that the circumstances which affect the patients (including cultural level) in mass campaigns developed in low-income countries may affect the visual records. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 2 3 In West Africa, the prevalence of cataract in adults is 40 years and older range from 21% to 62.1%. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation